E-SERVICE QUALITY TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN DALAM PENGGUNAAN INTERNET BANKING - Ni Made Savitri Anggraeni; Ni Nyoman Kerti Yasa (University of Merdeka Malang, 2012)
Banking industry had developed rapidly. It caused the competition and increasing the number of customersbecame difficult. An optimal e-service quality expected to meet the expectations of customers, so the companywas able to win the market competition and it would eventually bring the maximum profit. The objective of thisresearch was to know the effect of e-service quality towards customer satisfaction and loyalty in using internetbanking of Commonwealth Bank Seminyak Bali Branch. Respondents of this research were customers whoused internet banking at least twice a month in the last three years. The number of respondents on this researchdefined 200 respondents by using sampling technique namely purposive sampling. This research used analysisof Structural Equation. The result of this research showed that the hypothesis put forward entirely acceptable:e-service quality had positive and significant impact on satisfaction, e-service quality had positive andsignificant impact on loyalty, satisfaction had positive and significant impact on customer loyalty in usinginternet banking. Managerial implication of this research was that management should evaluate and fix theperformance of e-service quality in particularly web design quality and assurance that had been implementedto minimize customers complaint and to increase the customers satisfaction and loyalty.